The Scrapie Prevalence in a Goat Herd Is Underestimated by Using a Rapid Diagnostic Test - Konold, Timm; Spiropoulos, John; Thorne, Jemma; Phelan, Laura; Fothergill, Louise; Rajanayagam, Brenda; Floyd, Tobias; Vidana, Beatriz; Charnley, Judith; Coates, Nadya; Simmons, Marion (Frontiers in Bioengineering and Biotechnology, 2020)
Current European surveillance regulations for scrapie, a naturally occurring transmissible spongiform encephalopathy or prion disease in sheep and goats, require testing of fallen stock or healthy slaughter animals, and outline measures in the case of confirmation of disease. An outbreak of classical scrapie in a herd with 2500 goats led to the culling of the whole herd, providing the opportunity to examine a subset of goats, take samples and examine them for the presence of disease-associated prion protein (PrPSc) to provide further information on scrapie test sensitivity, pathology and association with prion protein genotype. Goats were examined clinically prior to cull, and the brains examined post mortem by Bio-Rad ELISA, a rapid screening test used for active surveillance in sheep and goats, and two confirmatory tests, Western blot and immunohistochemistry. Furthermore, up to ten lymphoid tissues were examined by immunohistochemistry. Of 151 goats examined, three (2.0%) tested positive for scrapie by ELISA on brain, confirmed by confirmatory tests, and a further five (3.3%) were negative by ELISA but positive by at least one of the confirmatory tests. Only two of these, both positive by ELISA, displayed evident signs of scrapie. In addition, ten (6.6%) goats, which also included two clinical suspects, were negative on brain examination but had detectable PrPSc in lymphoid tissue. PrPSc was detected most frequently in the medial retropharyngeal lymph node (94.4% of all 18 cases) and palatine tonsil (88.9%). Abnormal behavior and circling or loss of balance when blindfolded were the best clinical discriminators for scrapie status. None of the goats that carried a single allele in the prion protein gene associated with increased resistance to scrapie (Q211, K222, S146) were scrapie-positive, and the percentage of goats with these alleles was greater than expected from previous surveys. Significantly more goats that were scrapie-positive were isoleucine homozygous at codon 142 (II142). The results indicate that the sensitivity of the applied screening test is poor in goats compared to the confirmatory tests as gold standard, particularly for asymptomatic animals. Sensitivity of surveillance could be improved by testing retropharyngeal lymph node or palatine tonsil in addition to brain.